Design of High-Performance Electrospun Membranes for Protective Clothing Applications - Anca Filimon; Diana Serbezeanu; Daniela Rusu; Alexandra Bargan; Lavinia Lupa (Membranes)
The integration of nanomaterials into the textile industry has significantly advanced the development of high-performance fabrics, offering enhanced properties such as UV blocking, fire resistance, breathability, hydrophobicity, antimicrobial activity, and dust rejection. In this context, our research explores the development and characterization of electrospun membranes composed of polyether ether ketone (PEEK) and various polyimides (PIs (1–6)), focusing on their application in protective clothing. The combination of phosphorus-containing polyimides and PEEK, along with the electrospinning process, enhances the distinctive properties of both PEEK and polyimides, leading to composite membranes that stand out according to key parameters essential for maintaining physiological balance. The structural and morphological characteristics of these membranes have been evaluated using Fourier transform infrared spectroscopy (FTIR) to identify the functional groups and scanning electron microscopy (SEM) to examine their morphology. These analyses provide critical insights into these materials’ properties, which influence key performance parameters such as moisture management, breathability, and barrier functions. The membranes’ breathability and impermeability were assessed through the water vapor transmission rate (WVTR), contact angle measurements, water and air permeability, and flame resistance tests. The results obtained indicate that PEEK/polyimide composite membranes meet the complex requirements of modern protective textiles, ensuring both safety and comfort for users through their optimized structural properties and enhanced functional capabilities.